Development and Evaluation of 2-Amino-7-Fluorophenazine 5,10-Dioxide Polymeric Micelles as Antitumoral Agents for 4T1 Breast Cancer - Lecot, Nicole (2021)
2-Amino-7-fluorophenazine 5,10-dioxide (FNZ) is a bioreducible prodrug, poorly soluble in water, with potential anticancer activity on hypoxic-tumors. This poor solubility limits its potential applications in clinic. Amphiphilic pristine polymeric micelles (PMs) based on triblock copolymers Pluronic® and Tetronic®, glycosylated derivatives and their mixtures with preformed-liposomes (LPS), were analyzed as strategies to improve the bioavailability of FNZ. FNZ encapsulations were performed and the obtaining nanostructures were characterized using UV-visible spectroscopy (UV- VIS), Transmission Electron Microscopy (TEM), Fourier transform infrared analysis and Dynamic Light Scattering (DLS). The most promising nanoformulations were analyzed for their potential toxicity and pharmacologically, at 20 mg/kg FNZ-doses, in a stage-IV murine metastatic-breast tumor model. The results revealed that the solubility of the encapsulated-FNZ increased up to seven times and the analysis (UV-VIS, DLS and TEM) confirmed the interaction between vehicles and FNZ. In all the cases appropriate encapsulation efficiencies (up to 70%), monodisperse nanometric particle sizes (PDI = 0.180–0.335), adequate Z-potentials (-1.59 to -26.4 mV), stabilities and spherical morphologies were obtained. The in vitro profile of FNZ controlled releases corresponded mainly to a kinetic Higuchi model. The in vitro/in vivo biological studies revealed non-toxicity and relevant tumor-weight diminution (up to 61%).